KESADARAN PELAJAR SMAN 1 GUNUNG TULEH PADA DAMPAK KESEHATAN DAN HUKUM PERDATA DALAM MENCEGAH PERNIKAHAN DINI MELALUI EDUKASI PEMBERDAYAAN PERAN KELUARGA - Rizka Amelia; Khoirotunnisa, Elsa Aprilia, Hasan Maliki Anwar, Pradika Dwi Anggraini, Nabila Rizky, Solihin Nasuti (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Early marriage is a serious problem faced in Indonesia, including in Gunung Tuleh sub- district, West Pasaman Regency. This activity aimed to raise the awareness of students of SMAN 1 Gunung Tuleh about the health impacts and civil law in preventing early marriage through education on empowering the role of the family. This interactive socialization used various methods, including discussion and question and answer. The results showed an increase in students' knowledge of the dangers of early marriage, as well as an understanding of the role of the family in preventing it. It is hoped that this socialization can provide a comprehensive understanding of the negative impacts of early marriage on reproductive health, education, and economic welfare, thus contributing to a decrease in early marriage rates among adolescents in Gunung Tuleh